PERAN HUMAN RIGHTS WATCH (HRW) DALAM KONFLIK AGAMA DI INDIA 2019-2022 - Putra, Azlan Syah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research analyzes the role of Human Rights Watch (HRW) in Religious Conflict in India 2019-2022. Longing religion conflict become a serious problems for citizens of India,especially Indian Moeslem and international citizens. On December, 12nd. 2019, Indian government in Modi and Bharatiya Janaya Party (BJP) had passed the Indian Citizenship Act 2019 which is an amendment to the Citizenship Act 1955 which regulates the entry of immigrants from Afghanistan, Pakistan and Bangladesh based on the religion authorized in the Act. These include: Hindus, Buddhists, Sikhs, Christians, Jains and Parsis before 2015. However, the exclusion of Islam from the law caused massive protests throughout India. This research uses Qualitative methods, collection techniques through literature studies sourced from several books, journals, articles, websites, etc. This study also uses the perspective of constructivism and the Theory of International Organization. This research indicates that HRW has played a major role in the religious conflict in India by making investigative reports and reporting the results of his findings to the world, including the United Nations. Despite HRW has had a significant impact on the religious conflicts that occur in India, The Indian government actually refused to admit its actions and threatened HRW for interfering too much in its domestic affairs. Keywords: HRW, Religion Conflict, Citizenship Act, India